Contributions of the PilatesAR project to the treatment of musculoskeletal pain during the covid-19 pandemic - Dias, Fernanda Moura Vargas; Heringer Gama, Laís; Olegário Aguiar Pavesi, Raíssa; Karoliny Amparo Cardoso, Anne; Sartório Tomazeli, Pedro; Dolci, Jacqueline; Cortes Caetano Matos, Beatriz; Santos de Souza, Lorrainny; Barroco de Freitas, Giselle; Quartarolo Vargas, Ingrid; Tatiyama Miyamoto, Samira (Guará Journal, 2025)
This article reports the contributions of the PilatesAR project, during the COVID-19 pandemic, for the treatment of musculoskeletal pain in women through remote Pilates services. The project performed since 2018 face-to-face, adapted its attendances to the remote format with the COVID-19 pandemic and the suspension of face-to-face activities at UFES. Patients with Rheumatoid Arthritis (RA) who already participated in the in-person sessions and others who were invited through social networks were selected. The participants were evaluated by video call. The Pilates protocol was divided into standing and sitting exercises. The consultations occurred in group through Google Meet, with one student demonstrating the exercises, and the others monitoring the patients’ performance. From September 2020 to October 2021, 162 patients were seen, but 35 dropped out before the end of the protocol. Difficulties were encountered with the equipment (cell phone and internet), the patient’s environment (inadequate chair, lighting, and space), and with understanding the exercises. The ease of access to the remote session provided an opportunity to practice Pilates with reduced risk of contamination by COVID-19. The remote care provided the maintenance of health care overcoming the barriers imposed by social isolation.
Keywords: Pilates; Musculoskeletal pain; Health teleservice; Covid-19